Experiences of healthcare practitioners providing nutrition care to people with cancer in New Zealand: A qualitative study - Rana Peniamina; Rachael Mira McLean
Aim: To explore the perspectives and experiences of healthcare practitioners in providing nutrition care to people with cancer in New Zealand. Methods: Semi-structured interviews were conducted with 16 New Zealand healthcare professionals (HCPs) practicing in specialist secondary and tertiary cancer care (both public and private) who had previously completed an online survey about nutrition in cancer care. Interviews were recorded and transcribed verbatim, and thematic analysis was undertaken. Results: Participants identified nutrition as important in cancer care, from diagnosis to survivorship, in order to maximise recovery and ongoing health. While participants reported that the best person to provide high-quality individualised nutrition care is a dietitian, other HCPs also have a role in nutrition care. Limited nutrition care is currently available, especially for those in rural areas, which impacts health and equity in cancer care. Participants identified a need for increased dietitian capacity in the workforce as well as a need for nutrition resources that were accessible and appropriate. Conclusion: The perspective of participants was that more must be done to provide nutrition care as part of cancer care in New Zealand to improve health and wellbeing among people with cancer.